2013
DOI: 10.1038/aja.2013.32
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence of endogenous hydrogen sulphide as a mediator of relaxation in human and rat bladder

Abstract: We investigated the expression of hydrogen sulphide (H 2 S) in human and rat lower urinary tract (including bladder, prostate and urethra) tissues, and we sought to determine whether H 2 S induces relaxation of human and Sprague-Dawley (SD) rat bladder strips. Human normal lower urinary tract tissue was obtained for the evaluation of endogenous H 2 S productivity using a sulphide-sensitive electrode and for the analysis of the expression levels of all three synthases of endogenous H 2 S, cystathionine b-syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 28 publications
(36 reference statements)
3
41
0
4
Order By: Relevance
“…Since H 2 S and its synthases are present in the lower urinary tract tissues of various species, it is believed that endogenous H 2 S might play a role in the physiological function of the bladder and/or in pathological conditions such as overactive bladder (11). It has been suggested that in DSM, H 2 S induces concentrationdependent contraction by stimulating tachykinins release and activation of NK 1 and NK 2 receptors (37).…”
mentioning
confidence: 99%
“…Since H 2 S and its synthases are present in the lower urinary tract tissues of various species, it is believed that endogenous H 2 S might play a role in the physiological function of the bladder and/or in pathological conditions such as overactive bladder (11). It has been suggested that in DSM, H 2 S induces concentrationdependent contraction by stimulating tachykinins release and activation of NK 1 and NK 2 receptors (37).…”
mentioning
confidence: 99%
“…The presence of H 2 S pathway has been also confirmed by using biopsy from cancer-free human prostate (Gai et al 2013). Moreover, Guo and coworkers have demonstrated that both cell activity and CBS/CSE protein levels are higher in the androgen-dependent prostate cancer cell LNCaP than in all the other cell lines evaluated and that dihydrotestosterone downregulates this activity.…”
Section: Hydrogen Sulfide and Human Prostatementioning
confidence: 79%
“…CSE and CBS were detected by immunohistochemistry in nerve fibers and are widely distributed within the smooth muscle layer of the pig bladder neck (Fernandes et al 2013a). CBS, CSE, and 3MST have been also shown to be present in rat bladder (Gai et al 2013). In mouse bladder, only the presence of CSE has been reported so far, (Matsunami et al 2012).…”
Section: Animal Studiesmentioning
confidence: 95%
See 2 more Smart Citations